(untitled) (Impetus, 2022)
This article of reflection goes back to the fact that culture is immersed in humanity, this identifies us as a society, since it is known that each population in the world has different ways of living, expressions, thoughts and habits that make them different, characterizing themselves within a society, even the oldest societies have been identified by their cultural legacy, which through rites, customs and traditions have shaped the essence as such of the way a population lives and coexists. Starting from the fact that culture is the way of life of a society, where customs and traditions that are obtained thanks to daily living and the passage of time begin to take root, but little by little, they are left and are left in something nothing More than, as history, they cause in this way a great affectation and threat to the cultural legacy, this is due to the constant evolution to which the human being is subjected, which will be inevitable. This happens in all cultures of the world, so Colombia is no exception, many Colombian regions have been identified that are culturally rich, but left in oblivion, as it is with the llanera culture, causing a great impact and affectation to the cultural legacy. It is shocking to see how people stop doing things that were culturally ingrained, but why does this forgetfulness begin to occur?